As características demográficas, socioeconômica e epidemiológicas das aposentadorias brasileiras - Kretzmann, Fernanda Giordani (2021)
In recent years, Brazilian social welfare policies (health, social security and social assistance) have been discussed, especially social security policies. There are several arguments that point to difficulties in maintaining the social security system in the country, such as the demographic transition, the existence of a deficit in social security bills, among others. Social security, along with other security policies, has the duty to provide, through services, incomes and pensions, social protection to citizens. However, the insurance (contributory) character of the social security policy must be considered, which makes it, at times, excluding. Faced with a complex and necessary system, the question is: what are the reasons for retirement in Brazil and what are the demographic, socioeconomic and epidemiological characteristics of retirees? To answer this question, the National Sample of the Longitudinal Study of Health and Well-Being of Elderly Brazilians (ELSI-Brasil) was used, with people aged 50 years or more, developed in 2015 and 2016. This dissertation aims to describe the main reasons for retirement in Brazil, and the demographic, socioeconomic and epidemiological characteristics of retirees, in addition to comparing the prevalence of reasons for retirement stratified by sex. The methodological conduct of this study is guided by a quantitative approach, with descriptive analysis of the results, based on theoretical references about Brazilian social welfare system, with an emphasis on social security and health policies. The main results of this study showed regional disparities between the different reasons for retirement, and differences and similarities between men and women in relation to this access. It also suggests that health, work and education conditions can influence getting a more advantageous retirement, as well as contributes to early retirements, better or worse perceptions of health, access to health and living conditions in old age. Discussing and understanding social security is a decisive factor that may determine the direction of Brazilian’s social security policies, that must be defended, as they are human achievements.